Investigation on the Influences of STEAM-Based Curriculum on Scientific Creativity of Elementary School Students - Tran, Ngoc-Huy; Huang, Chin-Fei; Hsiao, Kuo-Hung; Lin, Kuan-Li; Hung, Jeng-Fung (Frontiers in Education, 2021)
Up until now, there have been several different viewpoints on creativity in general and creativity in the science field in particular. Furthermore, STEAM (Science, Technology, Engineering, Arts, and Mathematics) education is increasingly successful and widespread around the world; however, few studies on its impact on scientific creativity exist. As a result, research into the influence of STEAM-based curriculum on students' scientific creativity is critical. Elementary school students were chosen to investigate in this research, and the main topic of STEAM-based curriculum is about a house-shaped money saving tube with the main concept of lock, which was developed and created by the authors' team. This research produced two phases of courses: lock science courses (two weeks) and STEAM-based courses (two weeks). In this study, sixty-six elementary students from two separate courses were divided into two groups: control and experimental. This research used a counterbalanced design. The control group took lock science courses first, then STEAM-based courses, while the experimental group did the opposite. As a pre-test and post-test, students in both groups were asked to complete the "Scientific Creativity Test" (Cronbach's α.87). The findings of the paired t-test study indicate that both the control and experimental groups have improved their scientific creativity significantly. However, only the fluency and flexibility components of scientific creativity (fluency, flexibility, and originality) showed considerable development, whereas the originality component remained unchanged. This research also found that after engaging in a STEAM-based curriculum, there was no substantial difference in scientific creativity between males and females. Further discussion is provided.